(untitled) (Research, Society and Development, 2021)
This systematic review and meta-analysis evaluated if ketorolac reduces the intensity of postoperative pain after impacted third molars surgery in adults compared to the use of tramadol. A comprehensive search was performed in the MEDLINE/PubMed, Scopus, Web of Science, LILACS, BBO, EMBASE, Cochrane Library, SIGLE and grey literature, in accordance with the PRISMA guidelines. The quality of the evidence was evaluated using the GRADE approach. Meta-analysis was performed on studies considered at low risk of bias. After duplicates removal, 4526 articles were identified, but only nine studies were included for qualitative analysis. After updating in 2021, four studies were added, totaling 13 studies included for qualitative analysis. Only two studies, classified at “low” risk of bias, were included in the meta-analysis of the primary outcome. The difference in means for pain intensity (moderate quality of evidence due to imprecision) was – 0.27 (95% CI = – 0.82 to 0.28; p = 0.34). Data from adverse effects (low quality of evidence due to very serious issues in imprecision) was just reported in one study at “low” risk of bias. Data was not heterogeneous (Chi2 test p = 0.14; I2 = 55%). It was not possible to evaluate any secondary outcomes (time to first rescue analgesic drug in h, total amount of analgesics consumed and adverse effects) due to low number of studies included. There is a lack of strong evidence to assure the superiority of ketorolac or tramadol in reducing the postoperative pain after extraction of impacted third molars.